Variation of Hair Follicle Counts among Different Scalp Areas: A Quantitative Histopathological Study - Rutnin, Suthinee; Chanprapaph, Kumutnart; Pakornphadungsit, Kallapan; Leerunyakul, Kanchana; Visessiri, Yingluck; Srisont, Smith; Suchonwanit, Poonkiat (Skin appendage disorders, 2022)
Introduction: Scalp biopsy is a standard method for the definitive diagnosis of alopecia. The hair count parameters of each scalp area remain unclear. This study aimed to determine hair count values at different scalp locations from histopathology and to establish reference values for each part of the scalp. Methods: We obtained biopsy specimens from the frontal, vertex, temporoparietal, and occipital areas of the scalps of normal deceased subjects. All specimens were evaluated for the number of follicular units, hair counts, hair types, and stages of the hair cycle. Results: In total, 240 specimens were collected from 60 cadavers. Across all scalp sites, the temporoparietal area showed the lowest mean hair count, number of follicular units, terminal and vellus hairs, and terminal-to-vellus hair ratio. The average anagen-to-telogen hair ratio was comparable across all scalp sites. This study did not observe a significant association of hair parameters with gender differences or increasing age in all scalp areas. Conclusions: The present study revealed the diversity of the hair index among different scalp areas and suggested that normal hair count values should be separately standardized on each scalp region. Our findings may provide useful reference values for the histopathological evaluation of hair disorders in Asians.